Pengaruh Efikasi Diri Terhadap Minat Berwirausaha Melalui Motivasi Sebagai Variabel Intervening - Putry, Nur Anita Chandra; Wardani, Dewi Kusuma; Jati, Deviska Panggalih (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2020)
This study aims to examine the effect of self-efficacy on entrepreneurial interest through motivation as an intervening variable. The population in this study were 186 students of the Faculty of Economics at the University of Sarjanawiyata Tamansiswa Yogyakarta both from Accounting and Management Study Programs. The sampling technique used in this study was snowball sampling while the data analysis used in this study was path analysis. The classical assumption test used in this research are normality test, multicollinerarity test and heteroscedasticity test. The results of this study prove that self-efficacy has a positive effect on motivation. The results of data processing shows that motivation has a positive effect on entrepreneurial interest while self-efficacy has no effect on entrepreneurial interest and self-efficacy has a positive effect on entrepreneurial interest through motivation as an intervening variable.